Discovery and characterization of complete genomes of 38 head-tailed proviruses in four predominant phyla of archaea - Tianqi Xu; Yimin Ni; Hailing Li; Shuang Wu; Shuling Yan; Lanming Chen; Yongxin Yu; Yongjie Wang (Microbiology Spectrum)
ABSTRACT Archaea play a significant role in natural ecosystems and the human body. Archaeal viruses exert a considerable influence on the structure and composition of archaeal communities and their associated ecological environments. The present study revealed the complete genomes of 38 archaeal head-tailed proviruses through comprehensive data mining. The hosts of these proviruses were identified as belonging to the following four dominant phyla: Halobacteriota, Thermoplasmatota, Thermoproteota, and Nanoarchaeota. In addition to the 14 proviruses of halophilic archaea related to the Graaviviridae family, the remaining proviruses exhibited limited genetic similarities to known (pro)viruses, suggesting the existence of 14 potential novel families. Of the 38 archaeal proviruses, 30 have the potential to lyse host cells. Eleven proviruses contain genes linked to antiviral defense mechanisms, including those involved in restriction modification (RM), clustered regularly interspaced short palindromic repeat (CRISPR)-associated (CRISPR–Cas) nucleases, defense island system associated with restriction-modification (DISARM), and DNA degradation (Dnd). Moreover, auxiliary metabolic genes were identified in the proviruses of Bathyarchaeia and Halobacteriota archaea, including those involved in carbohydrate and amino acid metabolism. Our findings indicate the diversity of archaeal viruses, their interactions with archaeal hosts, and their roles in the adaptation of the host.IMPORTANCEThe field of archaeal virology has seen a rapid expansion through the use of metagenomics, yet the diversity of these viruses remains largely uncharted. In this study, the complete genomes of 38 novel archaeal proviruses were identified for the following four dominant phyla: Halobacteriota, Thermoplasmatota, Thermoproteota, and Nanoarchaeota. Two families and six genera of Archaea were the first to be identified as hosts for viruses. The proviruses were found to contain diverse genes that were involved in distinct adaptation strategies of viruses to hosts. Our findings contribute to the expansion of the lineages of archaeal viruses and highlight their intricate interactions and essential roles in enabling host survival and adaptation to diverse environmental conditions.